2018
DOI: 10.1002/eap.1726
|View full text |Cite
|
Sign up to set email alerts
|

The limited contribution of large trees to annual biomass production in an old‐growth tropical forest

Abstract: Although the importance of large trees regarding biodiversity and carbon stock in old-growth forests is undeniable, their annual contribution to biomass production and carbon uptake remains poorly studied at the stand level. To clarify the role of large trees in biomass production, we used data of tree growth, mortality, and recruitment monitored during 20 yr in 10 4-ha plots in a species-rich tropical forest (Central African Republic). Using a random block design, three different silvicultural treatments, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
4
14
0
Order By: Relevance
“…In addition, we found that the increase in tree size with species richness and stand age had a significantly positive effect on forest productivity. This agrees with previous studies where large‐diameter trees could enhance forest productivity in these forests because large‐diameter trees have the ability to capture more light and compete against neighbours (Ligot et al, ; Xu et al, ). Stand age may affect biomass and productivity via changes in stand structure (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we found that the increase in tree size with species richness and stand age had a significantly positive effect on forest productivity. This agrees with previous studies where large‐diameter trees could enhance forest productivity in these forests because large‐diameter trees have the ability to capture more light and compete against neighbours (Ligot et al, ; Xu et al, ). Stand age may affect biomass and productivity via changes in stand structure (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…33 and Ligot et al . 34 . This was likely due to SD decreasing as DBH increased with stand age (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with theory, there is evidence that stand biomass of tropical and temperate forest plots, primarily determined by the size of the largest tree (Stegen et al, ), is one of the major drivers of forest productivity (Michaletz et al, ; Michaletz, Kerkhoff, & Enquist, ). Furthermore, given that tall trees sequester carbon at higher absolute rates compared to smaller trees (Stephenson et al, ), they are often strong contributors to the whole‐stand carbon flux (Fauset et al, ; Gholz, ; but see Ligot et al, ). These theoretical predictions, however, are expected to be modified by human land‐use or natural disturbances (Kerkhoff & Enquist, ; McDowell et al, ; see also Coomes, Holdaway, Kobe, Lines, & Allen, ; Muller‐Landau et al, ).…”
Section: Introductionmentioning
confidence: 99%